Hajdúböszörmény református orgonái - SZABÓ, Balázs (Studia Universitatis Babes-Bolyai Theologia Reformata Transylvanica, 2019)
Organs in the reformed churches of Hajdúböszörmény. The main churches in Hajdúböszörmény, both of remarkable size inherit two Angster-organs with 3 manuals. The older and bigger organ in the church of Bocskai Square was built 1902 with three manuals and 46 stops. All divisions are constructed with different windchests by using tubular pneumatic action: the great and pedal with cone chest, the second manual with Witzig-type pneumatic windchest and the third manual using the Angster-type pneumatic windchest. This is indeed a unique solution by Angster, later one he never used the Witzig-systhem again, for pneumatic windchests he used the Angster-type pneumatic construction. The organ in the Kálvin Square church was originally built 1899, with slider chests, tracker action and barker lever, pneumatic action for the stops. Angster rebuilt it in 1914, the organ received new Angster-type pneumatic windchests and a new console with roll-player mechanism with three manuals and 38 stops. After several modifications, the organ was reconstructed to its original state in 2014–2016 as the first pneumatic-reconstruction project in Hungary. The Bocskai Square organ is after improper reparations still unplayable, the congregation launched benefit concerts by professionals in November 2018 to gain bigger public attention to this organ-treasure.